Are area-level socioeconomic inequalities in obesity moderated by neighbourhood greenery? - Sungkavi Selvakumaran; Nyssa Hadgraft; Manoj Chandrabose; Suzanne Mavoa; Neville Owen; Takemi Sugiyama (BMC, 2024)
Abstract Background Reducing socioeconomic inequalities in obesity is a public health priority. Limited research exists on the role of neighbourhood environmental attributes in mitigating these inequalities. However, it has been shown that neighbourhoods with more greenery tend to have lower levels of socioeconomic inequalities in non-obesity health outcomes. We examined whether neighbourhood greenery moderates the association of area-level socioeconomic status (SES) with waist circumference. Methods Data from 3,261 middle-aged and older adults who participated in a national cohort study conducted in Australia (2011-12) were used. The outcome was objectively measured waist circumference. For area-level SES, a composite index of disadvantage based on census data was used. We used two measures of neighbourhood greenery: mean greenness and geographic size of greenspace. They were assessed using the Normalized Difference Vegetation Index (NDVI) within 0.5, 1, and 2 km radius buffers around participants' homes. The mean NDVI value within each buffer area was used for the former, and the geographic size of the area with NDVI ≥ 0.6 (dense greenery) was used for the latter. Results There was a significant negative association between area-level SES and waist circumference: one standard deviation higher score in the area-level SES indicator (less disadvantage) was associated with 1.76 cm (95% CI: -2.68, -0.83) lower waist circumference. Analyses stratified by greenery levels found similar significant associations in the areas with low and high levels of greenery but not in the areas with medium levels of greenery for both greenery measures within 1 km and 2 km buffers. Conclusions Consistent with previous studies, our study found that participants living in disadvantaged suburbs were likely to have a larger waist circumference than those living in advantaged suburbs. However, we also found that such socioeconomic inequalities in obesity were mitigated in the areas with medium levels of greenery for this sample of Australian adults. Our findings suggest that there may be an optimum level of greenery where inequalities in obesity are alleviated. Further research is needed to understand the mechanisms underlying these findings.